Successful reproduction of adenoviral gizzard erosion in 20-week-old SPF layer-type chickens and efficacious prophylaxis due to live vaccination with an apathogenic fowl adenovirus serotype 1 strain (CELO). Issue 2 (10th January 2020) - Grafl, Beatrice; Berger, Evelyn; Wernsdorf, Patricia; Hess, Michael
Abstract: Recently, outbreaks of adenoviral gizzard erosion (AGE) have been documented in pullets and layers housed free range and in enriched cage systems characterized by increased mortality and a negative impact on egg production. In the present study the pathogenicity of a fowl adenovirus serotype 1 (FAdV-1) field strain as well as the aetiological role of a FAdV-8a strain, both isolated from AGE affected pullets, were investigated in vivo in 20-week-old specific-pathogen-free (SPF) layer-type chickens. Furthermore, the efficacy of a single (week 17) and double (week 14 and 17) application of a live vaccine consisting of an apathogenic FAdV-1 (CELO strain) against challenge with virulent FAdV-1 was investigated. For the first time, AGE was successfully reproduced in adult birds after oral infection of 20-week-old SPF birds with a virulent FAdV-1 field isolate, characterized by pathological changes of the gizzard from 7 days post challenge onwards. In addition, a negative impact of the FAdV-1 infection on the development of the reproductive tract was observed. Thus, confirming the pathogenicity and aetiological role of FAdV-1 in the development of AGE and economic losses due to AGE in layers. In contrast, no pathological changes were observed in birds infected with FAdV-8a. Independent of a single or double application of the live FAdV-1 vaccine strain CELO, no gross pathological changes were observed in gizzards post challenge with the virulent FAdV-1, indicating that complete protection of layers against horizontal induction of AGE was achieved. Nonetheless, virulent FAdV-1 was detected in cloacal swabs and gizzards in both vaccinated groups post challenge determined by the application of an amplification refractory mutation system quantitative PCR used to differentiate between vaccine and challenge strains.